Pengaruh Promosi, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung Di BeeJay Bakau Resort (BJBR) Kota Probolinggo - Wulandari, Nuril; Ngatimun, Ngatimun; Rahajeng, Yekti (Universitas Panca Marga, 2024)
The research aims to determine the influence of promotion, price and service quality on visitor satisfaction at BeeJay Bakau Resort (BJBR) Probolinggo City. The research method used is quantitative with a causal associative approach with variables consisting of independent variables, namely promotion, price and visitor satisfaction, while the dependent variable is employee performance. The population in this study was 168 visitors and the sample used was 118 visitors based on a purposive sampling technique. The analysis method uses validity tests, discriminant validity tests, reliability tests, normality tests and hypothesis tests with the help of SmartPLS 3.0. This research data uses primary and secondary data. The results of the research show that the Promotion variable (X1) has no effect on Visitor Satisfaction (Y), the Price Variable (X2) has an effect on Visitor Satisfaction (Y), while the Service Quality Variable (X3) has an effect on Visitor Satisfaction (Y) then it is proven that if the hypothesis is accepted the Work Motivation variable has a significant effect on performance.